(untitled) (New York, 1984)
This book examines the technologies of servive industries and how they are transferred to developing countries. Services are the just-of-the-boat immigranst in the eyes of most economic theorists, and as such have been more ignored than understood.
Keywords: Dịch vụ công nghiệp,Service industries; Các nước phát triển,Trường hợp nghiên cứu,Developing countries,Case studies